2015
DOI: 10.1371/journal.pone.0135975
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Time-Point Serum Cortisol and ACTH Measurements for the Adjustment of Glucocorticoid Replacement in Adrenal Insufficiency

Abstract: BackgroundAdjustment of daily hydrocortisone dose on clinical criteria lacks sensitivity for fine tuning. Long term hydrocortisone (HC) over-replacement may lead to increased morbidity and mortality in patients with adrenal insufficiency (AI). Biochemical criteria may help detecting over- or under-replacement but have been poorly evaluated.MethodsMulticenter, institutional, pharmacokinetic study on ACTH and cortisol plasma profiles during HC replacement in 27 AI patients compared to 29 matched controls. All AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…No consensus exists concerning the ideal surveillance of GC therapy in SAI. While the importance of clinical signs and symptoms is generally accepted, the usefulness of hormonal assessment for dose adjustment of GC therapy is an unsettled issue [13][14][15]. An alarming high incidence of adrenal crises despite patient education has recently been shown in AI.…”
Section: National German Audit Of Diagnosis Treatment and Teaching mentioning
confidence: 99%
“…No consensus exists concerning the ideal surveillance of GC therapy in SAI. While the importance of clinical signs and symptoms is generally accepted, the usefulness of hormonal assessment for dose adjustment of GC therapy is an unsettled issue [13][14][15]. An alarming high incidence of adrenal crises despite patient education has recently been shown in AI.…”
Section: National German Audit Of Diagnosis Treatment and Teaching mentioning
confidence: 99%
“…A study by Rousseau et al showed a good correlation between plasma cortisol measured at 10 am and the area under curve measured for cortisol between 8 am and 7 pm in 27 patients with Addison's disease treated with hydrocortisone taken in 3 doses per day. These authors showed that cortisol level at 10 am was a good predictor of the diurnal physiological profile of plasma cortisol, using healthy volunteers as a reference [49]; • 24 hour urinary free cortisol: UFC is affected by the saturation of CBG (a strong increase in UFC is seen in this case, even if plasma cortisol is low) and is thus not useful for adjusting the dose of hydrocortisone; • salivary cortisol is a cheap, feasible and reproducible test.…”
Section: Adult Patientsmentioning
confidence: 99%
“…A pilot study showed no significant difference between patients and female control subjects, but a difference was observed between male subjects [52]; • plasma ACTH: plasma ACTH does not assist in evaluating glucocorticoid replacement therapy with classic rapid release hydrocortisone since ACTH is always high in the morning on waking and then decreases rapidly after administration of hydrocortisone in primary adrenal insufficiency [53]. In the study by Rousseau et al, the amplitude of the fall in ACTH after the morning administration of hydrocortisone correlated less well with area under the curve for cortisol than cortisol measured at the morning peak of 10 am [49].…”
Section: Adult Patientsmentioning
confidence: 99%
“…Three previous open prospective studies have reduced the dose of conventional hydrocortisone (HC) replacement by 30-50 % (approximately 30 to 20-15 mg of HC per day) and found an increase in bone formation markers and a small reduction in body weight, but with no impact on blood pressure or glucose metabolism [3][4][5]. In addition, one open study which randomised patients to two different regimens of glucocorticoid replacement using doses between 15 and 30 mg of HC per day was unable to show an impact of dose on QoL [6].Based on the pharmacokinetic properties of conventional oral immediate-release HC formulations, it is impossible to achieve a physiological serum cortisol profile as there is a rapid increase in serum cortisol after an oral administration and a rapid decrease reaching low unphysiological troughs in between each dose [7,8]. The early morning rise in serum cortisol before awakening will not be mimicked using conventional HC.…”
mentioning
confidence: 99%
“…Based on the pharmacokinetic properties of conventional oral immediate-release HC formulations, it is impossible to achieve a physiological serum cortisol profile as there is a rapid increase in serum cortisol after an oral administration and a rapid decrease reaching low unphysiological troughs in between each dose [7,8]. The early morning rise in serum cortisol before awakening will not be mimicked using conventional HC.…”
mentioning
confidence: 99%